An application of interdependence theory to military medical research teams: Cultural noise, tradeoffs, and meaning. Issue 1 (3rd April 2018) - Lawless, W. F.; Wood, Joseph; Stachura, Maximillian E.; Wood, Elena A.
ABSTRACT: To better manage costs and effectiveness of a team or enterprise, the organizational sciences, social sciences and medical field are seeking new theory to transform teams and enterprises with computational models of complex social behavior that create "smart" systems. We have proposed to fulfill these calls with new theory, but ours is still under development. In a field application, we studied an electronic Institutional Review Board (eIRB) operating across a large complex of military medical scientists and researchers in Department of Defense (DoD) hospitals and clinics. As part of a field study of how the eIRB has transformed processes for DoD, we completed three comparable focus groups at a small and three focus groups at a large research site, one focus group of the eIRB's system managers, and one focus group of a competing eIRB operating in DoD (the latter group results are not reviewed at this time). We found tentative support for our theory: more noise (entropy) is being generated at the small site along with less research performed; cultural noise at both sites reflected an intransigence by sites to be transformed by adopting standardized forms; and the meaning of the findings differed between the small and large sites.